Sirtuin 1 inhibition delays cyst formation in autosomal-dominant polycystic kidney disease - Zhou, Xia (American Society for Clinical Investigation, 2013)
Autosomal-dominant polycystic kidney disease (ADPKD) is caused by mutations in either PKD1 or PKD2 and is characterized by the development of multiple bilateral renal cysts that replace normal kidney tissue. Here, we used Pkd1 mutant mouse models to demonstrate that the nicotinamide adenine dinucleotide–dependent (NAD-dependent) protein deacetylase sirtuin 1 (SIRT1) is involved in the pathophysiology of ADPKD. SIRT1 was upregulated through c-MYC in embryonic and postnatal Pkd1-mutant mouse renal epithelial cells and tissues and could be induced by TNF-α, which is present in cyst fluid during cyst development. Double conditional knockouts of Pkd1 and Sirt1 demonstrated delayed renal cyst formation in postnatal mouse kidneys compared with mice with single conditional knockout of Pkd1. Furthermore, treatment with a pan-sirtuin inhibitor (nicotinamide) or a SIRT1-specific inhibitor (EX-527) delayed cyst growth in Pkd1 knockout mouse embryonic kidneys, Pkd1 conditional knockout postnatal kidneys, and Pkd1 hypomorphic kidneys. Increased SIRT1 expression in Pkd1 mutant renal epithelial cells regulated cystic epithelial cell proliferation through deacetylation and phosphorylation of Rb and regulated cystic epithelial cell death through deacetylation of p53. This newly identified role of SIRT1 signaling in cystic renal epithelial cells provides the opportunity to develop unique therapeutic strategies for ADPKD.